Thailand : Technical Assistance Report-Government Finance Statistics. (IMF Staff Country Reports; Country Report ;, 2018)
The main purpose of this mission-undertaken with the support of the Government of Japan's government finance statistics (GFS) project for selected Asian countries-was to improve the quality of the GFS for nonfinancial public corporations (NFPCs) in Thailand by designing a simpler, but more complete, compilation system for the GFS compilers in the Fiscal Policy Office (FPO) of the Ministry of Finance. The mission also discussed some specific general government GFS data compilation issues with the compilers and recommended some actions that would lead to further improvements in data quality as well as consistency with other macroeconomic statistics. In addition, the mission commended the recent momentum gained by the Public Debt Management Office (PDMO) on the reporting of timely, quarterly public sector debt statistics and encouraged them to continue with the regular, quarterly reporting.